PROKSI UNTUK MENGUKUR TINGKAT KEPERCAYAAN DAN TINGKAT MOTIVASI DALAM KNOWLEDGE SHARING MAHASISWA DI KELAS APLIKASI INFORMASI AKUNTANSI - Rohmah, Aida (Jurnal Bisnis Darmajaya, 2016)
The science of knowledge develops because of the discussion and sharing among scientists. Therefore, knowledge sharing is one of important factor in improving student knowledge. The level of understanding of students, especially in practical classes will be more increased if the students share knowledge with the others students. Often the explanation lecturer missed because the student busy with their laptop or personal computer respectively. Therefore, the role of other students to help other students become essential to improve the students understanding.This research follow-up study of the Moon and Sensuse (2012) that have examined the factors that influence knowledge sharing. Months of research and Sensue (2012) simply states the hypothesis that individual factors have positive influence on knowledge sharing, but a proxy for measuring the individual factors (trust and motivation levels) have not been disclosed. Therefore, this researchpurposes to present a proxy that can be used to measure the trust level and the motivation level.Keywords: Knowledge sharing and accounting class, the trust of level, the motivation level.